Elastic and elasto-plastic buckling analysis of perforated steel plates - Real, Mauro de Vasconcellos; Isoldi, Liércio André; Damas, Alexandra Pinto; Helbig, Daniel (VETOR - Revista de Ciências Exatas e Engenharias, 2013)
Many steel structures such as ships and offshore structures are composed by welded stiffened or unstiffened plate elements. Cutouts are often provided in these plate elements for inspection, maintenance, and service purposes, and the size of these holes could be significant. In many situations, these plates are subjected to axial compressive forces which make them prone to instability or buckling. If the plate is slender, the buckling is elastic. However, if the plate is sturdy, it buckles in the plastic range causing the so-called inelastic (or elasto-plastic) buckling. Furthermore, the presence of these holes redistributes the membrane stresses in the plate and may cause significant reduction in its strength in addition to changing its buckling characteristics. So, the objective of this paper is to investigate the changes that the presence of circular holes produces in the elastic and inelastic buckling of steel rectangular plates. The finite element method (FEM) has been used to evaluate the elastic and elasto-plastic buckling load of uniaxially loaded rectangular plates with circular cutouts. By varying the hole diameter, the plate aspect ratio and the plate thickness during the analyses, the changes in the plate buckling behavior can be determined. The results show that while the circular hole can in some cases even increase the elastic buckling load, the elasto-plastic buckling load is reduced by the presence of the cutout.